Optical trapping of nanoparticles by ultrashort laser pulses. (28th March 2013) - Usman, Anwar; Chiang, Wei-Yi; Masuhara, Hiroshi
Optical trapping with continuous-wave lasers has been a fascinating field in the optical manipulation. It has become a powerful tool for manipulating micrometer-sized objects, and has been widely applied in physics, chemistry, biology, material, and colloidal science. Replacing the continuous-wave- with pulsed-mode laser in optical trapping has already revealed some novel phenomena, including the stable trap, modifiable trapping positions, and controllable directional ejections of particles in nanometer scales. Due to two distinctive features; impulsive peak powers and relaxation time between consecutive pulses, the optical trapping with the laser pulses has been demonstrated to have some advantages over conventional continuous-wave lasers, particularly when the particles are within Rayleigh approximation. This would open unprecedented opportunities in both fundamental science and application. This Review summarizes recent advances in the optical trapping with laser pulses and discusses the electromagnetic formulations and physical interpretations of the new phenomena. Its aim is rather to show how beautiful and promising this field will be, and to encourage the in-depth study of this field.